Strategi Guru Pendidikan Pancasila Dalam Meningkatkan Pemahaman Siswa Mengenai Keadilan Gender di SMKN 5 Surabaya - Purnamasari, Arum (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to reveal the strategies of Pancasila Education teachers in improving students’ understanding of gender justice at SMK Negeri 5 Surabaya. This study uses a qualitative research approach with a descriptive research method. The theory used in the study is Vygotsky’s constructivism theory in the implementation of strategies by teachers. This study was conducted at SMK Negeri 5 Surabaya by conducting in-depth interviews, documentation of supporting files, and direct observation of two Pancasila Education teachers. From this study, it resulted in a discussion that students previously had an understanding of gender justice, but of course improvements were needed due to factors in the form of technological developments and improvements in student quality and the importance of gender justice values themselves. In implementing this strategy, there is a very large role for teachers so that the objectives of the strategy can be achieved optimally. There are five forms of strategies carried out by Pancasila Education teachers in improving students’ understanding of gender justice, namely by compiling gender-responsive learning modules, creating gender-emotional LKPD, implementing gender-sensitive Problem Based Learning learning models, making teachers role models, and conducting gender learning evaluations.